The Relationship Between Achievement Motivation and Students’ Statistical Literacy in Statistics Learning - Azis Azis; Jarnawi Afgani Dahlan (Jurnal Penelitian dan Pembelajaran Matematika, 2026)
This study aims to analyze the relationship between achievement motivation and statistical literacy among mathematics education students. Statistical literacy is an important competency that enables students to understand, interpret, and use statistical information in various contexts. This study employed a quantitative approach with a correlational research design. The population consisted of mathematics education students who had taken statistics courses, while the sample included 23 students selected through purposive sampling. The research instruments consisted of a statistical literacy test comprising 15 items and an achievement motivation questionnaire consisting of 20 statements using a Likert scale. Data were analyzed using descriptive and inferential statistics, including normality test, linearity test, autocorrelation test, heteroscedasticity test, Pearson correlation analysis, coefficient of determination, and simple linear regression analysis. The results showed that students’ statistical literacy was in the moderate category with a mean score of 17.65, while achievement motivation was in the high category with a mean score of 75.96. The correlation analysis indicated a strong and significant relationship between achievement motivation and statistical literacy with a correlation coefficient of 0.782 and a significance value of 0.000. The regression analysis revealed that achievement motivation had a significant effect on students’ statistical literacy with a contribution of 61.2%. These findings indicate that achievement motivation is an important factor that can improve students’ statistical literacy in statistics learning.